Buffer effect and price effect of a personal carbon trading scheme. (15th March 2015) - Fan, Jin; Wang, Shanyong; Wu, Yanrui; Li, Jun; Zhao, Dingtao
Abstract: PCT (personal carbon trading) is a downstream cap-and-trade scheme used to reduce carbon emissions from the household sector. It is argued that the PCT scheme could provide a buffer between the energy price and the total energy price, and thus energy demand remains stable. However these effects have never been verified. To fill in this gap in the literature, a price effect analysis is conducted. Firstly, a GUO (general utility optimization) model is proposed to obtain the general formulae of the price effect, substitution effect and income effect under the PCT scheme. Secondly, a specific version of the GUO model, namely a Cobb–Douglas utility function model, is employed to obtain the specific effect formulae to verify the buffer effect. Finally, a numerical example and a sensitive analysis are presented to demonstrate these effects. The results indicate that, under the PCT scheme, the total energy price and energy demand are less sensitive to the energy price changes. Thus, when energy prices fluctuate, the PCT scheme is capable of providing certainty in emissions reduction and is more effective than carbon taxes. On the basis of these results, implications of this research are discussed and suggestions for future research are provided. Highlights: Utility optimization models are proposed to obtain the formulae of the price effect. Total energy price and energy demand are less sensitive to the energy price changes. The PCT scheme is capable of providing certainty in emissions reduction.